The Theory of Justice and Ultra petita Decisions: A Critical Analysis of Judicial Review in the Constitutional Court - Eza Tri Yandy; Tri Endah Karya Lestiyani (Constitutionale, 2025)
Under Law Number 24 of 2003, the Constitutional Court of Indonesia issues three types of decisions: inadmissibility, acceptance, and rejection. Over time, the Court introduced additional categories, including conditional constitutional and conditional unconstitutional decisions. As legal disputes have become increasingly complex, the Court has also issued ultra petita rulings, granting decisions beyond the scope of the petitioner's request. This research examines the evolution of justice theories and their relevance to the ultra petita decisions in judicial review cases. Using a normative legal research approach with conceptual and case-based methodologies, this research analyzes legislative texts, books, journals, and research reports through qualitative descriptive techniques. The findings reveal varying philosophical perspectives on justice: Plato views justice as intrinsic harmony, Aristotle differentiates between general and specific (proportional) justice, and John Rawls emphasizes fairness through the "original position" and "veil of ignorance." The ultra petita ruling in Case 90/PUU-XXI/2023 altered the presidential and vice-presidential age requirement by adding the qualification of previously holding an elected regional position. Meanwhile, Case 60/PUU-XXII/2024 redefined the regional head nomination threshold, setting aside the 20% DPRD seat or 25% vote requirement. Both decisions reflect procedural and substantive justice, ensuring fair outcomes. However, to prevent judicial overreach and uphold legal certainty, clear regulations on the Constitutional Court’s authority in issuing ultra petita decisions are essential..